Successive addition of two different Grignard reagents to nitriles: access to α, α-disubstituted propargylamine derivatives. Issue 9 (8th February 2018) - Caillé, Julien; Boukattaya, Fatma; Boeda, Fabien; Pearson-Long, Morwenna S. M.; Ammar, Houcine; Bertus, Philippe
Abstract : The successive addition of two different Grignard reagents to acyl cyanohydrins was performed with success by using alkynyl Grignard reagents. Abstract : The successive addition of two different Grignard reagents to acyl cyanohydrins was performed with success by taking advantage of the low reactivity of alkynyl Grignard reagents. The experimental conditions were adjusted so that they were not reactive during the first addition step, but reactive only in the second one. The synthetic utility of the prepared compounds was validated by the preparation of chiral quaternary α-amino acids.